PEMBINAAN NILAI TOLERANSI BERAGAMA DI PONDOK PESANTREN ANNURIYYAH SOKO TUNGGAL SEMARANG - Jamaluddin, Eko Wahyu; Suprayogi, Suprayogi; Munandar, Aris (Unnes Civic Education Journal, 2015)
SokoTunggal Islamic Boarding School Semarang has a very important role as a place to nurture religious tolerance for its students. The need for religious tolerance education is urgent because various conflicts in Indonesia are sourced from inter-religious issues. Religious tolerance education in Soko Sole Boarding School aims at nurturing mental and morals of the students in order to become a person with ahlakul karimah showed by tolerance to differences in people’s lives, especially religious differences. The results suggest the pesantren sucesfully conducts such program because the background of the Kyai , who is very tolerant, and the vision, mission and purpose of boarding school to teach the value of tolerance. Religious tolerance value is fostered through the habituation of students in interaction with people of other religions, the example of Kyai, and through learning, especially the books of morals. The factors that asupport the development of tolerance in the boarding school include: the competence of management, and the high motivation of the students. While inhibiting factor is the caretaker and students who also have other jobs so they are not always able to follow the activities of the boarding school and the damage of some infrastructure.